A Demodulation Method of Spatial Domain for Low-Coherence Interferometry With High Accuracy and Adaptability - Chao Wang; Xuezhi Zhang; Junfeng Jiang; Kun Liu; Shuang Wang; Yuanyao Li; Tiegen Liu (IEEE Photonics Journal, 2020)
A demodulation method of spatial domain based on low-coherence interferometry is proposed. The original signal of spatial domain acquired by linear CCD is filtered with all-phase filter to obtain the fringe pattern, and the phase signal of the spatial frequency domain is retained after filtering. The fringe pattern analysis is employed to avoid phase ambiguity and realize large measurement range in demodulation. Afterwards, using the centroid position of the fringe, the peak position of a single fringe pattern can be obtained, and finally the accurate peak position is calculated with seven-step phase-shifting interferometry. The demodulation method is demonstrated experimentally with Fabry-Perot sensing system. At room temperature, it is proved that the full-scale measurement error is less than 0.019% in the range of 11 kPa to 290 kPa. From −20 °C to 70 °C, the accuracy is stable and the maximum error is less than 0.054 kPa. The demodulation method has the potential to enhance the measurement accuracy and adaptability in actual environment for universal applications.